Combined serial section-based 3D reconstruction of cervical carcinoma invasion using H&E/p16INK4a/CD3 alternate staining. - Wentzensen, N.; Braumann, U. D.; Einenkel, J.; Horn, L. C.; von Knebel Doeberitz, M.; Loffler, M.; Kuska, J. P. (Cytometry A, 2007)
BACKGROUND: Malignant growth and invasiveness of cancers is a function of both intratumoral and stromal factors. The accessibility to nutrients, oxygen and growth factors, the stromal composition, and the interference with the immune system all shape the tumor invasion front. A recent study has shown a prognostic difference with respect to different invasion patterns analyzed on histological specimens of cervical cancers. The present study analyzes the spatial organization of a cervical cancer and the relation of the tumor invasion front and the infiltration with CD3(+) T-cells. METHODS: From a cervical squamous cell carcinoma specimen, 84 serial sections were performed and three interleaving series were stained with hematoxylin/eosin and immunohistochemistry directed against the cervical carcinoma biomarker p16(INK4a) and the T-cell marker CD3. Sections were passed through an image processing chain to obtain a reconstructed and segmented tissue volume. For local tumor invasion front analysis the mean curvature was used, which in turn was related to the respective local minimum tumor to T-cell distance as well to a T-cell originated diffusing substance's concentration at the tumor surface. RESULTS: Spatial models of the tumor tissue and the infiltrating T-cells were computed. The overall discrete compactness of the tumor invasion front was 0.89, corresponding to a pathological assessment of diffuse infiltration. The comparison of the tumor invasion front with the density of T-cell infiltration revealed an increased smoothening in regions with high T-cell infiltration. CONCLUSIONS: We could demonstrate the spatial organization of a cervical cancer and model the interaction between infiltrating T-cells with the tumor invasion front shape. Increased smoothening in regions with high T-cell infiltration suggests that T-cells may have an influence on the shaping of the tumor invasion front, e.g., by attacking tumor cells displaying specific antigens. The applied technique allows visualization of the spatial organization of tissues and could be extended to analyze multiple stains on alternating sections.
Keywords: CD3 Complex/*analysis/metabolism; Cyclin-Dependent Kinase Inhibitor p16/*analysis/metabolism; Female; Humans; Image Processing, Computer-Assisted/*methods; Neoplasm Invasiveness; Staining and Labeling; T-Lymphocytes/cytology/immunology; Uterine Cervical Neoplasms/immunology/*metabolism/*pathology